DISTILASI BERTINGKAT BIOETANOL DARI BUAH MAJA (Aegle Marmelos L.) - moh arif batutah (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2017)
This research of bioethanol processed from fruit maja (Aegle Marmelos L.), the process consists of two stages of fermentation and ethanol fractional distillation for the separation of water with a temperature of 78Â°C. The fermentation process 5-day produces ethanol content of 60% in the first distillation, fractional distillation is then performed to obtain the ethanol content above 90% and 4 times distilled into ethanol optimal levels above 90%. This distillation produces ethanol content of 92%. etonal content analysis results obtained 92.19%, Î¼ 1.498, Ï 0.8371 , 9546.223 calorific value, flash point: +21, pour point 60áµ’C not frozen and PH 5.